The opportunity cost of arthroplasty training in orthopaedic surgery. Issue 5 (October 2022) - Kelly, M.A.; Vukanic, D.; McAnena, P.; Quinlan, J.F.
Abstract: Introduction: Training the next generation of surgeons is a crucial role fulfilled by consultant orthopaedic surgeons. However we are increasingly constrained by limited time and resources. We sought to compare operative time and length of stay (LOS) for total hip and total knee arthroplasties (THA, TKA) performed by a consultant orthopaedic surgeon with those performed by supervised trainees. Materials and methods: A prospective database of arthroplasty procedures performed from 2015 to 2018 was collated. Primary surgeon grade was recorded. Patient demographics, ASA grade, LOS and operative time were recorded. For THA both cemented and uncemented arthroplasties were used. SPSS version 23 was used for statistical analysis. Results: 394 arthroplasty procedures were carried out during the study period. Trainee surgeons performed a high proportion of both THA (53.2%, n = 123) and TKA (44.8%, n = 73) surgeries. Trainees performed 57% of cemented THA procedures. LOS did not differ between consultant and trainee surgeons for THA (5.9 ± 4.8 days) or TKA (5.6 ± 4.1 days). Age had a significant effect on LOS (p < 0.001). For THA the mean operative time for trainees was 90.3 ± 19.23 min, 18.2 min longer than the consultant group. For TKA the mean operative time was 89.06 ± 18.87 min for trainees, 24.4 min longer than the consultant group. Discussion: At our institution trainee surgeons can be expected to take between 18 and 24 min longer to perform arthroplasty procedures. This should be factored into resource planning, as the training of orthopaedic surgeons is crucial to sustaining and improving health service provision. Highlights: Training the next generations of surgeons is a crucial role of consultant surgeons. We measured length of stay and operative time in an arthroplasty training unit. Trainees took longer to perform procedures but length of stay did not differ. This small time difference can be factored into education and resource planning.